Effect of acid etching time on bond strength of an etch-andrinse adhesive to primary tooth dentine affected by amelogenesis imperfecta - NORIKO HIRAISHI, CYNTHIA KAR YUNG YIU & NIGEL MARTYN KING (IAPD and Blackwell, 2008)
Amelogenesis imperfecta (AI) affects the deposition, mineralization and maturation of enamel in both the primary and the permanent dentitions, as a result of specific genetic defects. The diagnosis of AI frequently presents with sensitive and discoloured teeth. Poor dental aesthetics is the result of surface roughness, staining and abnormal crown shapes from enamel loss.